Prevalence of HCV genotypes in Poland – the EpiTer study - Flisiak, Robert; Pogorzelska, Joanna; Berak, Hanna; Horban, Andrzej; Orłowska, Iwona; Simon, Krzysztof; Tuchendler, Ewelina; Madej, Grzegorz; Piekarska, Anna; Jabłkowski, Maciej; Deroń, Zbigniew; Mazur, Włodzimierz; et al. (Clinical and Experimental Hepatology, 2016)
The aim of the study was to assess current prevalence of hepatitis C virus (HCV) genotypes in Poland, including their geographic distribution and changes in a given period of time. Material and methods : Data were collected with questionnaires from 29 Polish centers and included data of patients diagnosed with HCV infection between 1 January 2013 and 31 March 2016. Results : In total, data of 9800 patients were reported. The highest prevalence was estimated for genotype 1b (81.7%), followed by 3 (11.3%), 4 (3.5%), 1a (3.2%) and 2 (0.2%). Genotype 5 or 6 was reported in 6 patients only (0.1%). The highest prevalence of genotype 1 was observed in central (łódzkie, mazowieckie, świętokrzyskie), eastern (lubelskie) and southern (małopolskie, śląskie) Poland. The highest rate for genotype 3 was observed in south-western (dolnośląskie, lubuskie) and eastern (podlaskie, warmińsko-mazurskie and podkarpackie) Poland. Compared to historical data, we observed an increasing tendency of G1 prevalence from 72.0% in 2003 to 87.5% in 2016, which was accompanied by a decrease of G3 (17.9% vs. 9.1%) and G4 (9.0% vs. 3.1%). Conclusions : Almost 85% of patients with HCV in Poland are infected with genotype 1 (almost exclusively subgenotype 1b), and its prevalence shows an increasing tendency, accompanied by a decrease of genotypes 3 and 4.